THE DOMINANT LEARNING STYLES AMONG ELEVENTH-GRADE STUDENTS AT MAN 1 MAKASSAR - L, Sulfitriani; Korompot, Chairil Anwar; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study aims to identify the dominant learning styles among eleventh-grade students at MAN 1 Makassar. A descriptive quantitative research design was used, with data collected through a learning style questionnaire and a speaking performance test. A purposive sample of 30 students participated in the study. The findings show that the auditory learning style was the most preferred, chosen by 14 students (47%), followed by the visual learning style (10 students or 33%) and the kinesthetic learning style (6 students or 20%). These findings suggest that students' learning styles influence their speaking performance and highlight the importance of using varied teaching strategies to support learners with different preferences.